Balancing act: optimizing blue light for melanogenesis while minimizing cellular damage in primary human skin cells - Barolet, Augustin C.; Magne, Brice; Ferland, Karel; Uzunbajakava, Natallia E.; Barolet, Daniel; Germain, Lucie (Frontiers in Physiology, 2025)
IntroductionRecent findings show that visible light, particularly blue light, stimulates melanogenesis in human skin, though the underlying mechanisms remain debated. This study aimed to determine the cell damage threshold of non-ionizing blue light on keratinocytes while preserving their ability to stimulate melanogenesis.MethodsHuman keratinocytes (N = 3) and melanocytes (N = 3) were isolated from skin samples of varying Fitzpatrick skin phototypes and irradiated with blue light (λpeak = 457 nm) and UVA light (λpeak = 385 nm). Cellular metabolic activity was assessed using the AlamarBlue HS assay, α-Melanocyte-Stimulating Hormone (α-MSH) production by keratinocytes was quantified using ELISA, and Western blotting was used to assess pro-melanogenic factor expression in melanocytes.ResultsHigh blue light intensity (50 mW/cm2, 50 J/cm2) and UVA light (15 mW/cm2, 20 J/cm2) significantly reduced cellular metabolic activity, with a 0.86 ± 0.055 and 0.60 ± 0.031 (mean ± SD) fold decrease compared to their respective sham by day 7. In contrast, moderate blue light intensities (5–15 mW/cm2, 10–20 J/cm2) preserved cellular metabolic activity while stimulating α-MSH production, with an optimal balance achieved at 10 mW/cm2, 15 J/cm2 (1.14 ± 0.046 fold increase relative to sham on day 7). Co-culture experiments confirmed that irradiated keratinocytes enhanced melanogenesis in melanocytes via paracrine signaling, increasing the expression of Tyrosinase and Dopachrome Tautomerase (DCT). Direct blue light irradiation on melanocytes also increased pigmentation without significant cellular damage.DiscussionModerate-intensity blue light at 10 mW/cm2, 15 J/cm2 effectively stimulates melanogenesis while maintaining cellular metabolic activity in both keratinocytes and melanocytes, offering a promising, safe approach for blue light therapies targeting pigmentation disorders.